Training on making learning videos using Ms. PowerPoint and Fastone Capture at MTs Muhammadiyah 6 Bayat - Muhammad Ridlo Yuwono; Septiana Wijayanti; Triyono Triyono; M. Wahid Syaifuddin; Fery Firmansah; Joko Sungkono; Tasari Tasari; Yuliana Yuliana (Community Empowerment, 2022)
The purpose of this community service program is to train MTs Muhammadiyah PK Bayat teachers how to create learning videos with Ms. PowerPoint and Fastone Capture. Face-to-face training in the form of material for making learning video content using Ms. PowerPoint and screen recording using Fastone Capture was used in this program. Participants be able to make learning videos using Ms. PowerPoint and Fastone Capture as an outcome of this training session.